Political governance and power dispute in unit 071 of the National Pedagogical University - Bastiani Gómez , José (2024)
The article analyzes the political mobilization of the Central Commission group and the struggle for power in the dispute to govern in Unit 071 of the National Pedagogical University (UPN) in Chiapas, Mexico, in the midst of neoliberal policy in higher education. The qualitative positioning and use of ethnography, through participant observation, data were collected from three moments in the power dispute: appointment of the director, resignation due to closure of university facilities and persistence of the struggle to maintain the form of governance. Documentary research was carried out on the theory of governance and power, in addition to applying an observation guide and semi-structured interview to obtain empirical information on events that occurred at the university. Among the results, the absence of autonomy in the decision-making of the Unit was identified in the face of the apparent decentralization of the Ajusco Unit, which aggravates the struggle for power in Unit 071 in Chiapas. It is necessary that the state educational authorities establish a reform of the decree creating the UPN in order to avoid conflicts, and pay for financial and educational autonomy to avoid financial, social exclusion and job insecurity in the professionalization of teaching in the face of processes of globalization in the national and international context in the desire to promote educational governance.